KERAJINAN TANGAN HERBARIUM DI DESA PULAU SEMAMBU KECAMATAN INDERALAYA KABUPATEN OGAN ILIR - Marieska Verawaty (Politeknik Negeri Sriwijaya, 2019)
Activity of Community service (PPM) as part of The Tri Dharma Perguruan Tinggi has been done on October 2015. The activity was about